Kebijakan Kenormalan Baru Destinasi Wisata di Kabupaten Kulon Progo - Dyah Mutiarin; Fitri Lianawati; Janianton Damanik (Pusaka: Journal of Tourism, Hospitality, Travel and Business Event, 2022)
Tourism is one of the sectors most affected by the COVID-19 outbreak in in Kulon Progo regency. Efforts to restore tourism from COVID-19 must be comprehensive and sustainable. This article is intended to describe the new normal policy of COVID-19 on tourist destinations in Kulon Progo regency. This study uses a descriptive qualitative method analysis. The results revealed that the tourism sector during the pandemic and the new normal era must implement (1) health protocols for the tourist destinations by paying attention to cleanliness, health, safety, and environmental sustainability (CHSE) by providing hygiene facilities such as hand washing tools, soap, hand sanitizers, and temperature checks, (2) Applying ‘sambanggo’, (3) Limiting the number of visitors to prevent crowds and provide a safe distance to minimize spread, and (4) Tourist destinations are opened step by step.